GA Optimized Fractional Controller for a Wind Turbine Ride Through Pitch Malfunction - Pandiyan, Surya (2021)
This paper is about better integration of wind energy into an electric grid, avoiding wind turbine pitch malfunction to become a failure. A fractional-order controller is used in the two-level converters of the wind turbine to reduce the voltage drops during the malfunction. The reduction is attained by an optimization problem for selection of the parameters of the fractional-order control. The optimization problem is a nonconvex one, solved by a genetic algorithm together with a model of the wind turbine pitch malfunction. Kriging metamodeling is used to assist in output prediction due its lower computational requirements and its ability to provide a value for the uncertainty of the estimate. A comparison between the Kriging metamodeling and the complete model is presented and conclusions are stated to show the advantage of the Kriging metamodeling.